(untitled) (Raparin Journal of Humanities (RJH), 2024)
The research aims to present perspective of Islamic securitizations (instruments), their characteristics, and how they can contribute to achieving economic development, by shedding light on the applying experience in leading Islamic countries, namely Malaysia, Saudi Arabia, and the Emirates. This research has applied the descriptive and analytical approach by addressing the nature of Islamic instruments, their characteristics and their developmental role. The research has concluded a number of results, the most important results are as follows: that Islamic securitization is one of the means that contribute to achieving economic development as an effective financing tool by linking the financial sector with the real economy, and it contributes to achieving economic development by financing investment projects and eliminating the problem of unemployment. Islamic securitization has achieved remarkable development in Malaysia, as the local securitization market in Malaysia is an important platform for government agencies and investment companies in securitizations. The ratio of Islamic securitizations to GDP in the Kingdom of Saudi Arabia increased from 24.7% in 2012 to 39.34% in 2020. The United Arab Emirates ranked first among the Gulf Cooperation Council countries in issuing Islamic securitization with an amount of 63.644 billion.